Fitur Baru Aplikasi BSI Mobile: Produk Mitraguna Berbasis Online dengan Skema Akad Musyarakah Mutanaqisa (MMQ) - Asep Saepul Malik Ibrahim; Asyari Hasan (Jurnal Ilmiah Ekonomi Islam, 2023)
The digitalization of Islamic banking has given birth to various new opportunities that can be utilized to increase financial inclusion for the community. The availability of easy-to-reach access and financial services is an important factor in increasing the productivity of Bank Syariah Indonesia (BSI) service products. Through the BSI mobile application, it is expected to be a new innovation that makes it easier for people to enjoy online partner financing services by implementing a sharia refinancing agreement with the al-bai' scheme in the context of musyarakah mutanaqisah (MMQ).